EKSPLORASI JENIS DAN PEMANFAATAN TUMBUHAN OBAT PADA MASYARAKAT SUKU MUNA DI PERMUKIMAN KOTA WUNA - Wa Ode Jumiarni; Oom Komalasari (Majalah Obat Tradisional, 2017)
Muna tribe in Kota Wuna Settlement has utilized various types of medicinal herbs. However, until nowthere has been no documented information about the scientific names and their utilization of the medicinal plant species in the area. The objective of this study was to determine the number and types of medicinal herbs used by the society in the study area, efficacy and organs of the plants are utilized. The research was conducted from January until November 2013, in Wuna City Settlement Tongkuno districts, Muna regency, Southeast Sulawesi Province. This research method used was survey and interview. Identification of the types of medicinal herbs was done by matching the characteristics that exist with images referring to the plant identification book. The results showed that there were 34 collections of plants that have medicinal properties traditionally utilized by the Muna tribes at Wuna City Settlement. Based on 34 types of plants that used, Based on 34 types of plants used, 31 species have been identified and 3 plants species have not been identified.